Measuring the perceptions of prospective teachers: Planning technology-based learning during the Covid-19 pandemic - Sudaryanto, Memet; Zainudin, M. (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2023)
Online learning planning presents unique challenges that aspiring teachers must prepare for. This study aims to identify potential teachers' perspectives on designing technology-based instruction. Competency dimensions were created based on the findings of focused group discussions (FGD) with teachers and lecturers, which resulted in aspects of social networking, managing digital identity, filtering, creating content, and reusing. Following the FGD, indicators of nine dimensions